Evaluation of Two Femoral Arterial Cannulae With Conventional Non‐Pulsatile and Alternative Pulsatile Flow in a Simulated Adult ECLS Circuit1. Issue 1 (4th November 2018) - Wang, Shigang; Force, Madison; Kunselman, Allen R.; Brehm, Christoph; Ündar, Akif
Abstract: The objective of this study is to evaluate the hemodynamic characteristics of two femoral arterial cannulae in terms of circuit pressure, pressure drop, and hemodynamic energy transmission under non‐pulsatile and pulsatile modes in a simulated adult extracorporeal life support (ECLS) system. The ECLS circuit consisted of i‐cor diagonal pump and console (Xenios AG, Heilbronn, Germany), an iLA membrane ventilator (Xenios AG), an 18 Fr or 16 Fr femoral arterial cannula (Xenios AG), and a 23/25 Fr Estech remote access perfusion (RAP) femoral venous cannula (San Ramon, CA, USA). The circuit was primed with lactated Ringer's solution and packed red blood cells to achieve a hematocrit of 35%. All trials were conducted at room temperature with flow rates of 1–4 L/min (1 L/min increments). The pulsatile flow settings were set at pulsatile frequency of 75 bpm and pulsatile amplitudes of 1000–4000 rpm (1000 rpm increments). Flow and pressure data were collected using a custom data acquisition system. Total hemodynamic energy (THE) is calculated by multiplying the ratio between the area under the hemodynamic power curve (∫flow × pressure dt) and the area under the pump flow curve (∫flow dt) by 1332. The pressure drop across the arterial cannula increased with increasing flow rate and decreasing cannula size. The pressure drops of 18 Fr and 16 Fr cannulae were 19.4–24.5 and 38.4–45.3 mm Hg at 1 L/min, 55.2–56.8 and 110.9–118.3 mm Hg at 2 L/min, 94.1–105.1 and 209.7–215.1 mm Hg at 3 L/min, and 169.2–172.6 and 376.4 mm Hg at 4 L/min, respectively. Pulsatile flow created more hemodynamic energy than non‐pulsatile flow, especially at lower flow rates. The percentages of THE loss across 18 Fr and 16 Fr cannula were 16.0–18.7 and 27.5–30.8% at 1 L/min, 35.1–35.7 and 52.3–53.8% at 2 L/min, 48.3–50.3 and 67.3–68.4% at 3 L/min and 62.9–63.1 and 79.0% at 4 L/min. The hemodynamic performance of the arterial cannula should be evaluated before use in clinical practice. The pressure drops and percentages of THE loss across two cannulae tested using human blood were higher compared to the manufacturer's data tested using water. The cannula size should be chosen to match the expected flow rate. In addition, this novel i‐cor ECLS system can provide non‐pulsatile and ECG‐synchronized pulsatile flow without significantly increasing the cannula pressure drop and hemodynamic energy loss.